SOCIAL SECURITY NETS FOR MARINE FISHERIES (Centre for Development Studies-WP318, 2001)
Social Security is achieved when deprivation or vulnerability is reduced or removed as a result of using social means, thereby, in the process, making lives and livelihoods more secure. However, provision of such social security measures is influenced by various supply and demand factors. This paper attempts to explain the provision of social security in the fisheries sector of Kerala State in south India. It enumerates the salient achievements and the problems faced by the state in providing concrete social security measures for fishworkers. They were a section of Kerala society that was initially left out of the development process. The study also shows how netting them back into the mainstream was not only the result of enlightened state policy, but also, the result of the collective action by the fishworkers themselves. Finally, the paper reflects on what more needs to be done to further improve the standard of living of the fishing communities in Kerala and to streamline the delivery of social security.